Role of the Microbiota in the Modulation of Vaccine Immune Responses - Ciabattini, Annalisa; Olivieri, Raffaela; Lazzeri, Elisa; Medaglini, Donata (Frontiers in Microbiology, 2019)
The human immune system and the microbiota co-evolve and their balanced relationship is based on crosstalk between the two systems through the course of life. This tight association and the overall composition and richness of the microbiota play an important role in the modulation of host immunity and may impact on the immune response to vaccination. The availability of innovative technologies, such as next-generation sequencing and correlated bioinformatics tools, allows a deeper investigation of the crosstalk between the microbiota and human immune responses. This review discusses the current knowledge on the influence of the microbiota on the immune response to vaccination and novel tools to deeply analyze the impact of the microbiome on vaccine responses.